Pig feeding with nontraditional products: fifty years of research at the Instituto de Ciencia Animal - Castro, Manuel; Martínez, Mayuly (Cuban Journal of Agricultural Science, 2016)
This study reports the main results obtained at the Instituto de Ciencia Animal since its creation up to 2014, on the use of local resources for feeding pigs. It also refers to the advances in the use of sugar cane and its derivates, which are biotechnologically obtained. The study shows its usefulness, effectiveness, and possibility for replacing imported raw matter. This research also refers to biochemical and physiological aspects of pigs. Keywords: feeding, pigs, products, agro-industrial by-products